2019
DOI: 10.4183/aeb.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis Identifies Potentially Key Differentially Expressed Genes and Pathways in Orbital Adipose Tissues of Patients with Thyroid Eye Disease

Abstract: Context. Thyroid eye disease (TED), an orbital inflammatory status, generally occurred in Graves' disease. Objective. This study aimed to acquire further insight into molecular mechanisms of TED, especially several key involved genes and pathways. Design. The microarray dataset GSE58331 including expression data for orbital adipose tissue samples, isolated from TED patients and normal controls, was downloaded from a publicly accessible Gene Expression Omnibus database. Differentially expressed genes (DEGs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Gopinath et al [3] demonstrated that cardiac calsequestrin gene CASQ2 was markedly up-regulated (~ 2.2-fold) in patients with the orbital disease and/or healthy people by microarray analysis. Zhu and Yang [7] indicated that POMC, IL-2, GNG3, CXCR4, TLR4, CSF1R, LPAR3 and CXCL8 were hub genes among many DEGs. It was also found that 71 DEGs were associated with TED in the comparative Toxicogenomics Database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gopinath et al [3] demonstrated that cardiac calsequestrin gene CASQ2 was markedly up-regulated (~ 2.2-fold) in patients with the orbital disease and/or healthy people by microarray analysis. Zhu and Yang [7] indicated that POMC, IL-2, GNG3, CXCR4, TLR4, CSF1R, LPAR3 and CXCL8 were hub genes among many DEGs. It was also found that 71 DEGs were associated with TED in the comparative Toxicogenomics Database.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to data limitation, the methods used for identifying genes with biological relevance in TED are also limited to differential expression analysis-based approaches. Although studies reported by Rosenbaum et al [6], Zhu and Yang [7] and Lee et al [8] identified some genes related to TED, the unicity of their approach may not help capture some highly TED-related genes. Thus, integrating multiple approaches may help identify the credible key genes associated with TED.…”
Section: Introductionmentioning
confidence: 96%
“…Penelitian lebih lanjut bahkan berhasil mengidentifikasikan setidaknya 12 gen (tabel 2) yang mengalami perubahan ekspresi (differentially expressed genes, DEG) pada sampel jaringan adiposa orbital, yang juga diperkirakan berkaitan dengan patofisiologi GO. (45,46) Tabel 1. Protein yang mengalami peningkatan ekspresi pada GO…”
Section: Patofisiologiunclassified
“…Proteomic investigations of ocular tissues from GO patients have identified 13 proteins (listed in Table 1 ) that are significantly overexpressed and that have connections to tissue inflammation, adipose tissue differentiation, lipid metabolism, and tissue remodeling. Furthermore, analysis of differentially expressed genes (DEGs) in orbital adipose tissue samples led to the identification of 12 hub genes (listed in Table 2 ) [ 33 , 34 ].…”
Section: Pathogenesismentioning
confidence: 99%